1995
DOI: 10.1079/bjn19950158
|View full text |Cite
|
Sign up to set email alerts
|

Long-term oral refeeding of patients with cirrhosis of the liver

Abstract: A previous study has shown that malnourished, clinically stable patients with liver cirrhosis are in protein and energy balance at their spontaneous dietary intake and that an improvement in nutritional status cannot be anticipated at this intake (Nielsen et al. 1993). In the present study we examined to what extent oral intake could be increased by nutritional support, and to what extent dietary protein would be retained with increased intake. The techniques used for balance studies were also validated since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0
11

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 27 publications
4
68
0
11
Order By: Relevance
“…Detailed studies have been undertaken on protein and nitrogen balance in these patients and consistent increases in their requirements clearly demonstrated. [12][13][14][15] However, there is no consensus in the data on energy expenditure, and thus energy requirements, in this patient population. [16][17][18][19][20][21][22] Plauth et al 23 recommended that energy requirements should be determined in patients with cirrhosis by measurement of their resting energy expenditure (REE) using indirect calorimetry.…”
mentioning
confidence: 99%
“…Detailed studies have been undertaken on protein and nitrogen balance in these patients and consistent increases in their requirements clearly demonstrated. [12][13][14][15] However, there is no consensus in the data on energy expenditure, and thus energy requirements, in this patient population. [16][17][18][19][20][21][22] Plauth et al 23 recommended that energy requirements should be determined in patients with cirrhosis by measurement of their resting energy expenditure (REE) using indirect calorimetry.…”
mentioning
confidence: 99%
“…Protein in older cirrhotic adults of HE [37][38][39][40] . Similar studies continued in the 1990's, showing that higher amounts of protein intake do not lead to worsening of hepatic encephalopathy [41,42,45] . In 2004 and 2005, two more studies were done to completely remove any doubt as to whether or not dietary protein is harmful in HE.…”
mentioning
confidence: 58%
“…Patients with a positive nitrogen balance, as a result of consuming 60-80 g of protein, saw their physical condition improve [40] . At protein intakes of 1-1.8 g/ kg/day, improved liver function has been noted [42] and at protein intakes of 1.5 g/kg, subjects improved more rapidly compared to a control group that consumed only 0.7 g/kg/d [24] . Gheorghe et al [44] has also demonstrated that at intakes of 1.2 g/kg/day, 79.7% of all patients showed improvement in mental status and decreases in blood ammonia level, regardless of tolerance to diet.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…49 Precipitants of HE include constipation, infection, gastrointestinal bleeding, sedative use and electrolyte disturbance, and these factors should be actively looked for and treated aggressively. Low protein diets were once advocated in the treatment and prevention of HE, but it is now recognised that high calorie and protein diets are well tolerated in patients with cirrhosis 50 and should be encouraged to counteract the pathological cachexia associated with advanced disease.…”
Section: The Treatment Of Hepatic Encephalopathymentioning
confidence: 99%